The effectiveness of cognitive behavioral therapy on decreasing health anxiety - saeed rezaei; afsaneh darabi; amir mohsen rahnedjat (فصلنامه ابن سینا, 2018)
Background: Hypochondria (health anxiety) is a condition in which a person is excessively and unduly worried about having a serious illness. This disorder puts a significant burden on health services. The purpose of this study was to determine the effect of cognitive behavioral therapy (CBT) on decreasing health anxiety. Materials and methods: For this purpose, out of the whole individuals referred to the health care centers in Islam-shahr city, Iran, 30 patients (9 male and 21 female) with hypochondria were selected with a convenience sampling technique and were randomly divided into experimental and control groups. The illness attitudes scale was administered for the pre-test. Then 10 CBT sessions were conducted for the experimental group. The control group received no intervention. The same test was administered to both groups as the post test and also after three months follow-up. Results: The results of analysis of mixed repeated measure showed that after CBT the means of the health anxiety in experimental group was significantly lower in comparison to the control group (p<0.001). Conclusion: This study showed that CBT is an effective intervention to decrease health anxiety.